POLAMAKAN DAN KADAR KOLESTEROL PADA PENDERITA STROKE - Ouslan, Rey Ivi (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Diet is an overview of the kind, number, and composition of food eaten every dayby the people that are characteristic of a particular group of people, the importance of the typeand content of food in order to avoid an increase in cholesterol, especially in patients withstroke. This research aimed to investigate the relationship between diet and cholesterol levelsin patients with stroke in hospitals Argamakmur. This research was a descriptive analyticcross sectional design. From the results of Chi-square (X2) X2 obtained count (6.9633)> X2tables (3,841), means there was relationship between diet with cholesterol levels in strokepatients in Arga Makmur Hospital of North Bengkulu. The result of this research wasexpected to respondents in Arga Makmur Hospital always follow a diet that was given inorder to speed up the healing process.